Photo-elicitation with adolescents in qualitative research: an example of its use in exploring family interactions in adolescent psychiatry - J. Sibeoni; E. Costa-Drolon; L. Poulmarc'h; S. Colin; M. Valentin; J. Pradère; A. Revah-Levy (BMC, 2017)
Abstract Background Photo-elicitation is a method used increasingly often in qualitative health research, and its positive effect on the research process is well established today. Photo-elicitation appears to facilitate verbalization and insight and to improve relationships between the researcher and participants, thereby enriching the quality of the data collected. Nonetheless, it is barely used at all in the field of adolescent psychiatry. With the aim of exploring the potential of these methods for research with adolescents receiving psychiatric care, we conducted a qualitative photo-elicitation data collection study with this population, asking them about family interactions around food. Methods The data were collected from 15 adolescents and 17 parents during semi-structured interviews in which a photo taken by the adolescent served as the focus of discussion. Data were explored through inductive thematic analysis. Results Photo-elicitation played a threefold role in this study: (1) it induced the teens' interest, thought, and pleasure, (2) it played a mediating function during the interviews, and (3) it enabled family interactions to be viewed from the adolescent's perspective. Three themes concerning family interactions were found: (1) parent-child relationship patterns, (2) the functioning of the family group, and (3) the adolescent's individual relation with food, that is, the issue of the adolescent's autonomy. Conclusions Photo-elicitation proved to be an innovative technique in qualitative research in the area of adolescent psychiatry, one that enriched the data and enabled the emergence of new themes in this field, related in particular to the process by which adolescents develop autonomy.